Cardiopulmonary dysfunction in the Osteogenesis imperfecta mouse model Aga2 and human patients are caused by bone-independent mechanisms - Thiele, Frank; Ivandic, Boris; Katus, Hugo (Human molecular genetics, 2012)
Osteogenesis imperfecta (OI) is an inherited connective tissue disorder with skeletal dysplasia of varying severity, predominantly caused by mutations in the collagen I genes (COL1A1/COL1A2). Extraskeletal findings such as cardiac and pulmonary complications are generally considered to be significant secondary features. Aga2, a murine model for human OI, was systemically analyzed in the German Mouse Clinic by means of in vivo and in vitro examinations of the cardiopulmonary system, to identify novel mechanisms accounting for perinatal lethality. Pulmonary and, especially, cardiac fibroblast of perinatal lethal Aga2/ animals display a strong down-regulation of Col1a1 transcripts in vivo and in vitro, resulting in a loss of extracellular matrix integrity. In addition, dysregulated gene expression of Nppa, different types of collagen and Agt in heart and lung tissue support a bone-independent vicious cycle of heart dysfunction, including hypertrophy, loss of myocardial matrix integrity, pulmonary hypertension, pneumonia and hypoxia leading to death in Aga2. These murine findings are corroborated by a pediatric OI cohort study, displaying significant progressive decline in pulmonary function and restrictive pulmonary disease independent of scoliosis. Most participants show mild cardiac valvular regurgitation, independent of pulmonary and skeletal findings. Data obtained from human OI patients and the mouse model Aga2 provide novel evidence for primary effects of type I collagen mutations on the heart and lung. The findings will have potential benefits of anticipatory clinical exams and early intervention in OI patients.